A Review on Manufacturing Operations of Solid Dosage Forms: Design and Implementation on GMP Systems in the Manufacturing Facility - Alex Joseph (Journal of Global Pharma Technology, 2018)
Manufacturing of solid dosage forms which should be performed accordance with the Good Manufacturing Guidelines as per the local regulatory requirements, Product quality cannot be adequately ensured only by inspecting and testing a finished product because finished-product testing cannot detect all defects, quality must be built into a product with processes that are well-controlled during design and manufacturing. Manufacturers need to establish and implement the quality design that controls each step in manufacturing process to ensure that the product meets predetermined specification. This study is anticipated to provide guidance which includes all the operations starting with procedure for obtaining the manufacturing license, procurement of raw materials and packing materials, handling in warehouse, production planning, dispensing, line clearance, in-process quality control tests, storage, sampling, analysis, approval and batch release.Keywords: Good manufacturing practice, Manufacturing license, IPQC.